2016
DOI: 10.1116/1.4962265
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine-induced elastic and adhesive changes of Escherichia coli cells within a biofilm

Abstract: Chlorhexidine is a widely used, commercially available cationic antiseptic. Although its mechanism of action on planktonic bacteria has been well explored, far fewer studies have examined its interaction with an established biofilm. The physical effects of chlorhexidine on a biofilm are particularly unknown. Here, the authors report the first observations of chlorhexidine-induced elastic and adhesive changes to single cells within a biofilm. The elastic changes are consistent with the proposed mechanism of act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Triclosan was found to interrupt the synthesis of phospholipids, lipopolysaccharides and lipoproteins by reacting with enzymes in the fatty acid synthesis pathway (Schweizer 2001;Maillard 2002). The biguanide components were confirmed to inhibit the activity of ATPase (Chopra et al 1987;Kuyyakanond and Quesnel 1992;Rodgers and Murdaugh 2016). This study showed that GA-DDAB had a significant effect on the activity of H + -ATPase.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Triclosan was found to interrupt the synthesis of phospholipids, lipopolysaccharides and lipoproteins by reacting with enzymes in the fatty acid synthesis pathway (Schweizer 2001;Maillard 2002). The biguanide components were confirmed to inhibit the activity of ATPase (Chopra et al 1987;Kuyyakanond and Quesnel 1992;Rodgers and Murdaugh 2016). This study showed that GA-DDAB had a significant effect on the activity of H + -ATPase.…”
Section: Discussionmentioning
confidence: 74%
“…The biguanide components were confirmed to inhibit the activity of ATPase (Chopra et al . ; Kuyyakanond and Quesnel ; Rodgers and Murdaugh ). This study showed that GA‐DDAB had a significant effect on the activity of H + ‐ATPase.…”
Section: Discussionmentioning
confidence: 99%
“…The high chlorhexidine concentrations commonly used in surface solutions (2–4%) limit the clinical implications of these data, which present a fundamental interest however. Nevertheless, it has been recently shown that medically relevant concentrations of chlorhexidine [0.1% and 1% (w/v)] increased the stiffness of E. coli biofilms [46].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have observed the effect of biocides on the biofilm mechanical response. 48 For instance, Pseudomonas aeruginosa and Streptococcus epidermis biofilms are modified by ciprofloxacin, glutaraldehyde, and urea. 46 The study of the time course of mechanical properties before and after a treatment allows the screening of new entities able to inhibit or delay the formation of biofilms.…”
Section: Biofilms Mechanics: a Microbiological Significancementioning
confidence: 99%
“…Moreover, one promising prospect is to combine chemical and mechanical strategies 42 , 47 to target viscoelastic properties of bacterial biofilms. The chemical treatment reduces the cohesiveness 49 or the stiffness 48 of biofilms, and thus decreases the force needed to eradicate them or enhance the diffusion of biocides within the EPS matrix. 50 The mechanical properties of biofilm could be used to probe quantitatively the biofilm cohesiveness, make clinical diagnoses, or adapt therapies to types of infection.…”
Section: Biofilms Mechanics: a Microbiological Significancementioning
confidence: 99%